Effects of schedules of reinforcement on pouched rats' performance in urban search‐and‐rescue training. Issue 1 (16th November 2015) - Edwards, Timothy L.; La Londe, Kate B.; Cox, Christophe; Weetjens, Bart; Poling, Alan
Abstract : Standard operating procedures have been developed to train Cricetomys to locate humans in collapsed structures and return to the release point on command. The present study demonstrated that the schedule of reinforcement for target location influences the rats' performance. Rats required more time to locate targets when no reinforcement was arranged for target location but less time to return to the release point. These findings suggest that training conditions should be based on the priority assigned to target location and return in an operational scenario.